Estimation of Dynamic Linear Expenditure Functions for Housing - Cronin, Francis J. (The Review of Economics and Statistics, 1982)
THE effectiveness of programs designed to improve the housing of low-income renter households by increasing their demand for housing through income supplements or price discounts has recently been questioned, based largely on the results of the Experimental Housing Allowance Program (EHAP). The results from EHAP generally indicate small consumption responses on the part of low-income households (i.e., inelastic price and income elasticities of demand for housing; see Friedman and Weinberg (1978), Mulford (1979), and Hanushek and Quigley (1979)). However, using a cross section of households sampled before the experiment began and a static linear expenditure specification, Cronin (1979) obtains static price elasticity estimates substantially exceeding in absolute value those estimated with experimental data (i. e., 0.53 to 1.00 for the former versus -0. 16 to -0.21 for the latter). The estimates of static current income elasticities (about 0.2 to 0.3) were similar to those found in EHAP. This paper extends the previous analysis by obtaining dynamic estimates of housing income and price elasticities from the linear expenditure system. Results indicate that the responsiveness of households may be greater than previously indicated. Short-run elasticities are found to be highly inelastic. However, when households are stratified by the time period since their move to allow for varying adjustment toward equilibrium, long-run elasticities are often found to approach unity. The conceptual framework for the analysis is presented in section II. Data, samples of households and definitions of variables are discussed in the first part of section III; results are presented and discussed in the second part.